PENELITIAN TINDAKAN: PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI MODEL ELICITING ACTIVITIES (MEA) - Muhammad Nurhusain (ELIPS: Jurnal Pendidikan Matematika, 2021)
Students' low creative thinking ability is one of the problems in the world of education. Therefore, a learning model is needed as a solution to these problems, through a model eliciting activities. This study aims to improve students' creative thinking ability through the application of the eliciting activities model. This study is a classroom action research (CAR). The subjects were class VIII students of SMP YP PGRI 4 Makassar registered in the academic year of 2020/2021, totaling 21 students. The results of the descriptive analysis show that the average value the students’ creative thinking ability in Pre-CAR at 50,38 with a standard deviation of 12,897, cycle I at 66,86 with standard deviation of 11,979, and cycle II at 81 with standard deviation of 10,798. Based on the students' creative thinking scores, as many as 14,29% (3 students) had high creative thinking ability in pre-CAR, and 42,86% (9 students) in cycle I, rose to 90,48% (19 students) in cycle II. So, the students’ creative thinking ability after cycle II are fulfilled in classical. The conclusion that can be explain is that the application of the eliciting activities model can improve the creative thinking ability of grade VIII students of SMP YP PGRI 4 Makassar.